Digital Logic is blowing my head off! I can't understand a thing.

I had a question in which I was supposed to simplify the function

Code:
F= A'+B'+(A+B).B'.C

apperently this simplify to 1.

Here's what I managed to do:

Code:
F= A'+B'+[(A.B')+(B.B')].C by Distribution

F= A'+B'+(A.B').C by Tautology

F= A'+B'+A.B'.C by Distribution

according to the answer the next step get

F = A+A'+B'

F=1

however I have no idea what he's done or how to get there.

Any help would be appreciated

Regards,
Bruynz.

I hope this is the right section

Last edited:

tiny-tim
Homework Helper
Welcome to PF!

Hi Bruynz! Welcome to PF! Digital Logic is blowing my head off! I can't understand a thing.

I had a question in which I was supposed to simplify the function

Code:
F= A'+B'+(A+B).B'.C

reality is at fault! The question is obviously wrong. F= A'+B'+(A+B).B'.C
F = A' + B' + A.B'.C
F = A' + B' + A.C
F = A' + B' + C

Yeah, they did something jive near the last step. I'm pretty sure that what I have down is the final answer. You can go back to the original and construct its truth table to trivially show it is no tautology.